Redução aluminotérmica do óxido de tântalo usando uma tocha de plasma como ignitor - Santos, Antonio Carlos Pereira (2007)
In this work was used a plasma torch of non transferred arc with argon as work gas, using a power supply with maximum DC current of 250 A and voltage of 30 V to activate the plasma and keep it switched on. The flame temperature was characterized by optical emission spectroscopy, through Boltzmann-plot-method. The torch has been used like igniter in the aluminothermic reduction of the mixture tantalum oxide and aluminum, seeking to obtain metallic tantalum. In heating of the reagents only one particle will be considered to study interactions between plasma-particle, seeking to determinate its fusion and residence time. The early powders were characterized by laser granulometry, scanning electron microscopy (SEM) and X-ray diffraction analysis. The final product of this reaction was characterized by SEM and X-ray diffraction. Crystallite size was calculated by the Scherrer equation and microdeformation was determined using Willamsom-Hall graph. With Rietveld method was possible to quantify the percentile in weight of the products obtained in the aluminothermic reaction. Semi-quantitative chemical analysis (EDS) confirmed the presence of metallic tantalum and Al2O3 as products of the reduction. As was waited the particle size of the metallic tantalum produced, presents values in nanometric scale due the short cooling time of those particles during the process